Keputusan Pembelian Ditinjau dari Lifestyle, Brand Image dan Kualitas Produk Kosmetik Merk Emina di Cabang Distributor Sinar Kosmetik Surakarta - Maylan Nur Arifin; Sri Hartono; Suparwi Pawenang (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This research aims to determine (1) the influence of Lifestyle on the decision to purchase Emina brand cosmetic products at the Sinar Kosmetik Surakarta store, (2) the influence of Brand Image on the decision to purchase Emina brand cosmetic products at the Sinar Kosmetik Surakarta store, (3) the influence of Product Quality on decisions purchase Emina brand cosmetic products at the Sinar Kosmetik Surakarta store. A quantitative descriptive design was used for this research. The population was taken from sales data for the last 3 months, with a sample size of 100 respondents. This research uses a purposive sampling technique. Data collection uses a questionnaire. The data analysis techniques used are statistical analysis, namely multiple linear regression test, F test, t test and coefficient of determination. The results show that Lifestyle has a significant influence on purchasing decisions for Emina brand cosmetic products at the Sinar Kosmetik Distributor Branch in Surakarta. Brand Image has a significant influence on purchasing decisions for Emina brand cosmetic products at the Sinar Kosmetik Distributor Branch in Surakarta. Product quality has a significant influence on purchasing decisions for Emina brand cosmetic products at the Sinar Kosmetik Distributor Branch in Surakarta